In Vitro Susceptibility to Ceftazidime-Avibactam and Comparator Antimicrobial Agents of Carbapenem-Resistant Enterobacterales Isolates - Tze-Peng Lim; Jun-Yuan Ho; Jocelyn Qi-Min Teo; James Heng-Chiak Sim; Si-Hui Tan; Thuan-Tong Tan; Andrea Lay-Hoon Kwa (Microorganisms, 2023)
The emergence of carbapenem-resistant Enterobacterales (CRE) has been recognized as a significant concern globally. Ceftazidime/avibactam (CZA) is a novel β-lactam/β-lactamase inhibitor that has demonstrated activity against isolates producing class A, C, and D β-lactamases. Here-in, we evaluated the in vitro activity of CZA and comparator antimicrobial agents against 858 CRE isolates, arising from the Southeast Asian region, collected from a large tertiary hospital in Singapore. These CRE isolates mainly comprised Klebsiella pneumoniae (50.5%), Escherichia coli (29.4%), and Enterobacter cloacae complex (17.1%). Susceptibility rates to levofloxacin, imipenem, meropenem, doripenem, aztreonam, piperacillin/tazobactam, cefepime, tigecycline, and polymyxin B were low. CZA was the most active β-lactam agent against 68.9% of the studied isolates, while amikacin was the most active agent among all comparator antibiotics (80% susceptibility). More than half of the studied isolates (51.4%) identified were Klebsiella pneumoniae carbapenemase (KPC)-2 producers, 25.9% were New Delhi metallo-β-lactamase (NDM) producers, and Oxacillinase (OXA)-48-like producers made up 10.7%. CZA was the most active β-lactam agent against KPC-2, OXA-48-like, and Imipenemase (IMI) producers (99.3% susceptible; MIC50/90: ≤1/2 mg/L). CZA had excellent activity against the non-carbapenemase-producing CRE (91.4% susceptible; MIC50/90: ≤1/8 mg/L). Expectedly, CZA had no activity against the metallo-β-lactamases (MBL)-producing CRE (NDM- and Imipenemase MBL (IMP) producers; 27.2% isolates), and the carbapenemase co-producing CRE (NDM + KPC, NDM + OXA-48-like, NDM + IMP; 3.0% isolates). CZA is a promising addition to our limited armamentarium against CRE infections, given the reasonably high susceptibility rates against these CRE isolates. Careful stewardship and rational dosing regimens are required to preserve CZA’s utility against CRE infections.